MENGURAI ETIKA SOSIAL BERBAGI NASI: KONSEP, NILAI, DAN DAMPAKNYA DALAM MASYARAKAT - Danang Nugroho; Erika Fauziah; Bayu Aprizal Nugraha; Hesti Friska Miranda; Hasni Lathifah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article explores the Social Ethics of Sharing Rice in Society. The purpose of his research is to understand the Concepts and Values underlying the practice of Sharing Rice and its social Impact on local communities. The research method used is the Descriptive Qualitative Method. In addition, embodied values such as social care, solidarity, empathy, justice, social responsibility and humanity become an integral part of social ethics in the context of sharing rice. In addition, an in-depth analysis was carried out related to the Impact of Sharing Rice in the Community such as to overcome hunger and food shortages, strengthen social relations and soldarity to maintain public health. The results of this study provide a more comprehensive insight into the Dynamics of Social Ethics in the practice of Sharing Rice and have important implications for the development of inclusive and sustainable social values and community policies. This article is expected to provide better insight into the concepts, values, and impacts of social ethics in the practice of sharing rice. With a deeper understanding of this, it is hoped that the community can continue to strengthen and expand the practice of sharing rice as a tangible form of solidarity and social care.